Analisis Total Fosfat pada Sampel Air Danau dengan Metode Spektrofotometri UV-Vis - Diana Ladies Novira; Jon Efendi (MASALIQ, 2026)
Total phosphate is an important parameter in water quality assessment because increased inputs can trigger eutrophication and disrupt the balance of aquatic ecosystems. This study aimed to determine total phosphate concentrations in lake water samples using the UV–Vis spectrophotometric method based on SNI 6989-31:2021 and to evaluate the consistency of the analytical results through quality control. The study employed a quantitative approach through laboratory analysis of three lake water samples. Measurements were performed using a UV–Vis spectrophotometer at a wavelength of 880 nm, while total phosphate concentrations were determined based on a linear calibration curve. Quality control was performed through duplicate and spike tests. The results showed that the total phosphate concentrations in Lake Samples 1, 2, and 3 were 0.019, 0.024, and 0.020 mg/L, respectively. The calibration curve yielded the equation y = 0.5528x + 0.0020, with a coefficient of determination (R²) of 0.9949, indicating a strong linear relationship between concentration and absorbance. The duplicate test yielded a relative percent difference (RPD) of 5.13%, indicating a relatively small difference between measurements, while the spike test yielded a total phosphate concentration of 0.449 mg/L after the addition of the standard. These findings confirm that the UV–Vis spectrophotometric method based on SNI 6989-31:2021 can be used to determine total phosphate concentrations in the lake water samples analyzed. The results of this study contribute analytical information that can support water quality monitoring and eutrophication risk control in lake ecosystems.